An integrated approach for modeling and identification of perfusion bioreactors via basis flux modes. (June 2021) - Rodrigues, Diogo; Abdalmoaty, Mohamed R.; Jacobsen, Elling W.; Chotteau, Véronique; Hjalmarsson, Håkan
Abstract: This paper discusses the challenges associated with the reliable and optimal operation of perfusion bioreactors and presents methods for modeling and identification of perfusion bioreactors as well as the vision for their integration. After presenting a generic model of perfusion bioreactors, the paper shows how to use the concept of basis flux modes to uniquely compute reaction rates. The advantage of this concept with respect to elementary flux nodes and similar concepts in metabolic flux analysis is the reduced number of flux modes that need to be modeled. In addition, a procedure to identify the model and estimate the parameters for each reaction using Monod-type kinetics is presented. It is shown that the rational structure of these kinetic models results in optimization problems that are amenable to tractable computation of globally optimal parameter estimates. The methods are illustrated via examples with simulated or experimental data.